A N-party authenticated group key distribution protocol using quantum-reflection architecture. (21st November 2022) - Zhu, Hongfeng; Du, Zhiqin; Wang, Liwei; Zhang, Yuanle
In this paper, quantum reflection security protocol is studied and an n -party authenticated group key distribution protocol based on quantum-reflection architecture is proposed. The N -AGKDP can implement identity authentication between participants and quickly distribute group key. In this protocol, a trusted third party sends the quantum sequence containing the session key through the quantum channel to the first ordered participant. And then by quantum-reflection technique, all the ordered participants can get the session key by delay line device and their own password or secret shared key with TTP. The protocol has a general structure for implementing the n -party PGKA program. In addition, we give an example of n = 3 so that readers can better understand our agreement. Compared with the traditional password-based group key protocol, our new protocol can resist the attack of quantum computers and is more secure.